Effect of Saline water and Potash Fertilizer on some chemical constituents in Pisum sativum L.(Var.Senador Cambados) plant. - Baghdad Science Journal (مجلة بغداد للعلوم)
Field experiment was conducted to test the effect of saline water and fertilizers rate on Pisum sativum L. plants . Treatments of the experiment included two levels of water salinity (2, 7 dSm-1) as a main plot and three levels of potash fertilization K2SO4 (44%K) namely 150 control, 300 and 450 kg/Donum as a sub plot. Results indicated that irrigation of plant with saline water 7 dSm-¹ caused a significant decrease in K and P contents specially in the upper parts of the plants , the percentage of the K increased (2.80%) under 2 dSm-¹of irrigation water and 300 kg/ donum fertilizer rate in the upper leaves, However K decreased(1.10%) in lower leaves under 7 dSm-¹ and 300 kg/donum fertilizer. while P increased in pods under same water salinity but with 150kg/ donum potash fertilizer. although P decreased( 0. 3 %) in pods under 7 dSm-¹ salinity water with 150 kg/donum fertilizer. However the results showed irrigation with 7 dSm-¹ saline water and 150kg/ donum fertilizer increased Ca, Mg and Na percentage ( 3.1 ,0.45 ,1.19 % ) in the roots of plants respectively , the lowest Ca ,Mg percentage was in pods of plants irrigated with 7 dSm-¹ saline water and fertilized with 150kg/ donum (0.39,0.05%), beside Na lowest percentage was ( 0.16 %) in upper leaves after using 2 dSm-¹ saline water and fertilized with 300kg/ donum. Accordingly, conclusion could be made that potassium fertilization may reduce the inhibitory effect of increasing salinity of irrigation water on pea.